NILAI-NILAI KARAKTER YANG DIKEMBANGKAN OLEH IBU RUMAH TANGGA DALAM MENJALANI TRADISI OTANG TENGKA - Riskiyah, Faridatur; Kholifah, Siti; Utaminingsih, Alifiulahtin (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
The significance of character values as shapers of the personality of the nation's golden generation can never be divorced from the actors involved as agents of socialization. This article seeks to explore the character values developed by housewives in the practice of the "otang tengka" tradition in Besuki Village, Besuki District, Situbondo Regency. The method employed is qualitative with a phenomenological approach. Informants were selected through purposive sampling to obtain relevant data. The research findings indicate that the character values developed by housewives in the practice of the "otang tengka" tradition are responsibility, cooperation, work ethic, and self-reliance. These character values are brought forth by housewives due to the demands of the "otang tengka" tradition, which compel them to participate in various tasks. In other words, the local tradition holds positive significance in the emergence of character values, making it worthy of preservation.